Evaluating development projects: exploring a synthesis model of the logical framework approach and outcome mapping - Yang, Ting (2018)
Under the current results-driven development agenda, sound evaluation, and a corresponding evaluation toolkit, need to be in place to examine whether and to what extent development interventions have achieved their targeted objectives and results, and to generate lessons for further development learning and improvement. My review of the literature shows that innovative and appropriate evaluation approaches are needed to address key challenges in evaluation such as the tension between learning and accountability objectives, the need to unpack the mechanisms linking outputs and outcomes or goal, and to add an actor perspective. Irrespective of project type, the Logical Framework Approach (LFA) is often a standard requirement of major official donor agencies on projects they fund, so as to fulfil bureaucratic imperatives. However, it is often considered inadequate in addressing key challenges in development evaluation. Given the dominant status of the LFA with such strong support from donors, it is helpful to seek a ‘middle way’: a combination of the LFA with other approaches in order to address some of its inadequacies, while satisfying donor agencies’ requirements. A synthesis of the LFA and Outcome Mapping (OM) is one such option. This thesis explores the practical value and usefulness of a synthesis model empirically. Applying the model in two case study aid projects, I found that it serves well as a theory-based evaluation tool with a double-stranded (actor strand and results chain) theory of change. The model helps reconcile learning and accountability and add explanatory power and an explicit actor perspective. It also helps establish causation and enable attribution claims at various results levels with its different elements. The model has some limitations but my results suggest it can be usefully adopted. The choice of its application depends on project evaluation context and purpose in specific cases.
Book Title: Evaluating development projects: exploring a synthesis model of the logical framework approach and outcome mapping

Matrixing Aid: The Rise and Fall of 'Results Initiatives' in Swedish Development Aid - Vähämäki, Janet (Stockholm Business School, Stockholm University, 2017)

Navigating by Judgment: Organizational Structure, Autonomy, and Country Context in Delivering Foreign Aid - Honig, Daniel (Harvard University, Graduate School of Arts & Sciences, 2015)
This dissertation examines when initiatives by International Development Organizations (IDOs) are more, and less, successful. The core argument is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most effective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public management and bureaucracy – would predict, with better performance resulting from less control. In the delivery of foreign aid the costs of monitoring to the principal are often overshadowed by the deleterious effects of the monitoring itself. The core of the argument is that development implementation requires soft information, tacit knowledge, and flexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in environments that are uncertain or difficult to understand from the outside and tasks where outputs are difficult to observe and/or poorly correlated with long term intervention goals. Insecure political authorizing environments which constrain the autonomy of IDOs prevent these organizations from Navigating by Judgment in situations where this is the best strategy. Empirically, this dissertation examines a cross-IDO dataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) and the UK’s Department for International Development (a higher autonomy IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT

Managing Upward and Downward Accountability in an International Development Project - A Case Study of a World Bank Telecommunications Infrastructure Project in Benin - Kolker, Eva; Kulldorff, Catharina (Master's Thesis, Stockholm School of Economics, 2013)
Keywords: Downward accountability; Upward accountability